Copper‐Incorporated Porous Polydivinylbenzene as Efficient and Recyclable Heterogeneous Catalyst in Ullmann Biaryl Ether Coupling. Issue 6 (25th January 2013) - Wang, Liang; Zhang, Jian; Sun, Jing; Zhu, Longfeng; Zhang, Haiyan; Liu, Fujian; Zheng, Dafang; Meng, Xiangju; Shi, Xiaodong; Xiao, Feng‐Shou
Abstract The preparation of efficient and stable heterogeneous catalyst is very important for organic transformations. Herein, we report a copper‐incorporated porous, Schiff base‐modified polydivinylbenzene (PDVB‐SB‐Cu) as an excellent heterogeneous catalyst in promoting Ullmann biaryl ether coupling reactions. PDVB‐SB‐Cu was synthesized by incorporating copper species into PDVB‐SB. Combined characterizations by using 13C NMR, IR, XPS, N2 adsorption, and TEM indicated the synthesis of copper–Schiff base species on porous PDVB. Catalytic tests in the Ullmann biaryl ether coupling of iodobenzene and phenol indicated that the PDVB‐SB‐Cu catalyst gave high activity similar to that of the homogeneous Schiff base‐stabilized copper catalyst. This good reactivity was likely due to the polymer‐based porous materials, which provided more effective interactions between substrates and catalytic centers. Importantly, PDVB‐SB‐Cu has extraordinary recyclability. The advantages of high activities and good recyclability made the PDVB‐SB‐Cu catalyst a new class of solid‐support transition metal catalysts for fine chemical preparation.